Insulin Receptor and the Kidney: Nephrocalcinosis in Patients with Recessive INSR Mutations - GÜRAN, TÜLAY (KARGER, 2014)
Background/Aims: Donohue and Rabson-Mendenhall syndrome are rare autosomal recessive disorders caused by mutations in the insulin receptor gene, INSR. Phenotypic features include extreme insulin resistance, linear growth retardation, paucity of fat and muscle, and soft tissue overgrowth. The insulin receptor is also expressed in the kidney, where animal data suggest it plays a role in glomerular function and blood pressure (BP) regulation, yet such a role in the human kidney is untested. Patients with biallelic INSR mutations provide a rare opportunity to ascertain its role in man. Methods: Retrospective review of patients with INSR mutations. Data for BP, renal imaging, plasma creatinine and electrolyte levels, as well as urine protein, albumin and calcium excretion were sought from the treating clinicians. Results: From 33 patients with INSR mutations, data were available for 17 patients. Plasma creatinine was low (mean +/- SD: 25 +/- 9 mu mol/l) and mean plasma electrolyte concentrations were within the normal range (n = 13). Systolic BP ranged between the 18th and 91st percentile for age, sex, height and weight (n = 9; mean +/- SD: 49 +/- 24). Twenty-four-hour urinary calcium data were available from 10 patients and revealed hyper-calciuria in all (mean +/- SD: 0.32 +/- 0.17 mmol/kg/day; normal < 0.1). Nephrocalcinosis was present in all patients (n = 17). Urinary albumin excretion (n = 7) ranged from 4.3-122.5 mu g/min (mean +/- SD: 32.4 +/- 41.0 mu g/min; normal <20). Conclusions: INSR dysfunction is associated with hypercalciuria and nephrocalcinosis. No other consistent abnormality of renal function was noted. Normotension and stable glomerular function with only moderate proteinuria is in contrast to genetically modified mice who have elevated BP and progressive diabetic nephropathy. (C) 2014 S. Karger AG, Basel
Keywords: RABSON-MENDENHALL SYNDROME; DIABETES-MELLITUS; DONOHUE SYNDROME; RESISTANCE; DELETION; GENE; DYSFUNCTION; ABSORPTION; CHANNELS; MICE